Connecting micro- and macroscopic variables in the design of a granular stirrer using simulations - Arévalo, Roberto (Frontiers in Soft Matter, 2023)
We present simulations of a stirrer used to mix a bed of identical spheres. The stirrer consists of a screw conveyor that rotates at fixed frequency enclosed in a vertical cylinder. Our goal is to improve the design (diameter of the cylinder) and operation (rotational frequency of the screw conveyor) of the stirrer to attain a good mixing. We characterize the mixing by some macroscopic measures and relate its behavior with the design parameters. Afterwards we compute some microscopic measurements that characterize the movement of the spheres and relate them with the operating conditions. Finally, some relations between microscopic and macroscopic measures are drawn. This approach can guide the design or operation of devices to handle granular media when their microscopic behavior is previously known. This is specially useful in the case of dense granular materials, since general theories able to predic their behavior are still lacking.